PELAKSANAAN PELAYANAN BARTENDER DI HOTEL NOVOTEL PEKANBARU - Tualang, Wy’ Akcdio Farub; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Molecule Gastro Bar was established with the Novotel hotel in 2016, located on Jalan Riau No.59, Senapelan District, Pekanbaru City. Molecule Gastro Bar and Hotel Novotel Pekanbaru are owned by PT. Crown Prince Raya. Molecule Gastro Bar is a modern bar at the Novotel Pekanbaru Hotel. Molecule Gastro Bar itself was built on a millennial and modern basis, not only following the tastes of alcoholic drink lovers, Molecule also follows trends in the tastes of non-alcoholic lovers, but Molecule Gastro Bar also follows the market and tastes of young people. This research uses a qualitative method with a descriptive approach to describe and display the conditions existing at the research location by collecting data and information obtained directly from the field. The key informants in this research are the Manager, Supervisor, Bartender and Guests who visit Molecule Gastro Bar. In this research, the data collection techniques used were interviews, observation and documentation. From this research it can be seen that Bartender service at Molecule Gastro Bar uses 4 elements, namely speed, accuracy, friendliness and skill. Of all the elements carried out by Bartender Molecule Gastro Bar, everything has been carried out well, although there are still several things that need to be improved. Keywords: Bar, Service, Novotel Pekanbaru